Chemical Characterization and Antibacterial Activity of Black Tea Extract Components - S., Mahdi H.; Kh., Mahdi L.; Y., Saour K. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Aqueous extracts of black tea exhibited antimicrobial activity against wide range of bacteria. Aim of study: In this investigation the antimicrobial ly active components of this extract were identified and characterized. The minimal inhibitory concentration (MIC) for each one was determined. Subject & Methods: the active components of the aqueous extract were identified and characterized. The minimal inhibitory concentration (MIC) for each was determined. Tannic acid, theophylline, caffeine and theobromine were isolated by thin layer chromatograhy (TLC) and purified by silica gel column. MIC was assessed by using agar dilution method. Results: Broad spectrum activity of three components excluding theobromine against gram- negative and selective gram-positive organisms was observed. Tannic acid showed the greatest potency with MIC of 160 /ig/ml. whereas the MIC of theophylline and caffeine was 2.5 mg/ml and 10 mg/ml respectively.